Ontogenetic features of redox reactions in the myocardium of geese - Yakoviichuk, О.; Danchenko, Olena; Данченко, Олена Олександрівна; Данченко, Елена Александровна; Kurtyak, B.; Nikolaeva, Y.; Fedorko, A.; Halko, T. (Lietuvos mokslp akademija, 2018)
Under conditions of physiological stress of different aetiologies, cells of any organism undergo compensatory metabolic changes. The specificity of such changes primarily depends on functional and histochemical features of the tissues of the body. The purpose of this work was to describe the functioning of the main components of the oxidation-reduction system, (ORS, the Krebs cycle, and the antioxidant system) in the myocardium of geese under conditions of the physiological stress occurring during the transition from the embryonic to postnatal development. It has been experimentally established that in the second half of geese embryogenesis, the content of short-chain fatty acids is significantly increased and the content of long-chain polyunsaturated fatty acids in their myocardium decreases. During the first two weeks of the postnatal period, there are reversible changes in the fatty acid composition of this tissue. The second half of the embryogenesis is characterized by the activation of dehydrogenases of the Krebs cycle in the low variability of antioxidant enzyme activity. At the same time, the experiment demonstrated an increase in the antioxidant activity coefficient, with the exception of its significant reduction on the first day of postnatal ontogenesis. The functioning of the ORS in the myocardium of geese is characterized by the presence of correlations between the nature of the changes of 19 investigated components (dehydrogenases of the Krebs cycle, antioxidant enzymes, lipid peroxidation products, antioxidant activity coefficient, fatty acids, their total content and unsaturation) and structuring of the system into two clusters
Keywords: dehydrogenase; Krebs cycle; fatty acids; antioxidant protection; hyperoxia; hypoxia